Description of Architectonics in the Work of Michael Kenningham “The Hours” - Khajieva Feruza Melsovna; Haydarova Nargiza Gulomjonovna (Central Asian Journal of Theoretical and Applied Science, 2022)
This article analyses the term architectonics through characters. The character in the novel “The Hours” will discuss different and unusual ways in English literature. The symbols perfectly have used in this literary work. Three women characters give special ideas about the novel. This novel is different in its style of writing and motif from other novels. In the case of all three women, the conflict is internal. Each woman fights against her own feelings of unhappiness with her life. Virginia Woolf struggles against insanity, Clarissa Vaughn fights her fear of mortality, and Laura Brown wrestles with her feelings of being trapped in her life as a housewife.